Knowledge production and patterns of proximity: French smes of biotechnology - Delphine Gallaud (European Regional Science Association (ERSA), 2002)
Nowadays, innovation is the main factor of firms and regions competitiveness. But, the conditions necessary to improve its development remain still unknown, particularly there are few works about spatial aspects of its appearance. Few monographs exist on the efficiency of 'local' networks, but no theoretical patterns. We want to check if innovative networks are really more efficient if they are local, and bring to the fore the conditions of this efficiency. This conditions seem to lie in the notion of proximity. Instead of considering geographic and organizational proximity as substitutes, we define them as complementary. So we propose a schedule of innovative networks linking geographic and organizational proximity. We shall test it in the biotechnology field, to build a typology of innovative networks. Key words: innovative networks, geographic and organizational proximity, biotechnology.
Keywords: 330